Az91d Magnezyum Alaşımının Mikro Ark Oksidasyonu Ve Mühürleme Yöntemi İle Yüzey Özelliklerinin İyileştirilmesi - Sener, Esra (Fen Bilimleri Enstitüsü, 2014)
Magnezyum ve alaşımları düşük yoğunlukları ve buna bağlı olarak hafif malzemeler olması nedeniyle birçok sanayi dalında ve günlük yaşamımızda tercih edilen bir malzeme olmuştur. Son zamanlarda öne çıkan çevre koruma çalışmaları, yeni düzenlenen yasalar ve sıkı denetimler nedeniyle  ticari faaliyetlerde  önlem alınmış, bunun için yeni projeler başlatılmıştır. Özellikle otomotiv sanayinde ortaya çıkan farkındalık birçok sanayi dalını da bu yönde cesaretlendirmiştir. Magnezyum burada ana malzeme olarak devreye girmiştir. Direksiyon simidinden motor bloğuna kadar aracın her parçasında kullanılabilen magnezyum otomotiv sektöründe araçların yakıt sarfiyatını minimuma indirerek hem daha ekonomik araçlar üretmek hem de zararlı gazların havaya salınımını önlemek amacıyla araçların hafifletme çalışmaları yapılmış, burada kullanılan birçok parça, mekanik özellikleri bakımından muadili olan malzemelerden yapılmaya başlanmıştır. Magnezyum da bu esnada otomotiv sektöründe kendine yer bulmuştur. Magnezyumun bu sektörlerde kabul görmeye başlaması kolay olmamış, bu alanda rakibi olan alüminyuma göre daha maliyet gerektirmesi magnezyumun öne çıkmasını bir nebze engellemiştir. Ancak hafif bir malzeme olan magnezyum lojistik açıdan yine diğer metallere göre avantaj sağlamaktadır. Magnezyum düşük yoğunluğunun yanı sıra kolay işlenebilmesi tercih edilmesi için başka bir nedendir. Ancak bunun yanında magnezyum oldukça aktif bir metal olduğu için korozyon nedeniyle kullanımı sınırlanmaktadır. Özellikle klor iyonlarına maruz kaldığında zarara uğrayan magnezyum bu açıdan ihtiyaçlara cevap vermekte zayıf kalabilmektedir. Bu durumda magnezyuma müdahale edilmesi ve istenilen değerlerin yakalanması gerekmektedir. Yüzey işlemle bu sorunun çözülmesi mümkündür. Yüzey işlem yöntemlerinden biri olan mikro ark oksidasyon işlemi magnezyum alaşımlarının yüzey özelliklerini geliştiren çalışmalardan biridir. Mikro ark oksidasyon işlemi elektrik akımıyla gerçekleştirilen, basit, ucuz ve çevre dostu bir yöntemdir. Kullanılan elektrolitin içeriğine bağlı olarak dışarıya çevreye zarar verebilecek kimyasal maddeler salınımı olmamaktadır. Bunun yanında elektrik enerjisiyle çalışan bir sistemden yararlanıldığı için fosil yakıt ihtiyacı bulunmamaktadır.  Sistem basitçe güç kaynağı, elektrolit, anot ve katot, kontrol paneli, soğutma sisteminden oluşmaktadır. Bu sistem ise şöyle çalışmaktadır; yüzey işlem yapılacak malzeme pozitif uca bağlanıp elektrolite daldırılır. Negatif uca ise katot malzeme bağlanır. Sisteme ilgili parametreler girilir ve işlem başlar. Uygulanan gerilim bozunum değerini geçtiğinde malzeme yüzeyinde lokal arklar oluşur. Böylece oksitlenme gerçekleşir. Bu yöntem akım kontrollü, gerilim kontrollü, çalışma rejimi kontrollü ya da vuruş kontrollü olarak çalıştırılabilmektedir. Böylece istenilen yüzey özellikleri elde edilene kadar bu parametreler değiştirilebilir. Mikro ark oksidasyon yöntemiyle istenilen yüzey sertliği, aşınma direnci ve yüzey pürüzlülüğü elektriksel parametrelerin yanı sıra elektrolit bileşimiyle de alakalıdır. Bu özelliklerin elde edilmesi için istenilen kimyasal bileşim kullanılabilmekle beraber buna çeşitli katkı maddeleri de konulup gerek mekanik gerekse görsel açıdan fark yaratılabilmektedir. Mikro ark oksidasyon işlemi yüzey özelliklerinin geliştirilmesi için oldukça uygun bir yöntem olmakla beraber bazı destek yöntemlere ihtiyaç duymaktadır. Mikro ark oksidasyonla kaplanmış magnezyum alaşımlarında seramik yüzey porlu yapısı nedeniyle her zaman yeterli korozyon direnci gösterememektedir. Bu yüzden ayrıca bir korumaya daha ihtiyaç duymaktadır. Mühürleme yöntemi boşluk doldurmaya ve izolasyon sağlamaya yönelik bir yöntem olduğu için, bu kaplamalardan sonra uygulanan yardımcı tekniklerden biridir. Bu yöntemle korozif etkinin porlar ve çatlaklardan yüzeye erişmesi engellenmekte, böylece daha malzeme daha uzun ömürlü olabilmektedir. Mühürleme yöntemi genellikle ısı ile mühürleme, soğuk mühürleme ve polimer son kat vb. şekilde kullanılmaktadır.  Mühürleme yöntemi poröz yüzeylerin özelliklerinin geliştirilmesi için gerekli bir çalışmadır. Birçok araştırmacı tarafından yürütülen çalışmalarda farklı mühürleme yöntemleri denenmiş ve sonuçları kullanıcılara sunulmuştur. Bu mühürleme yöntemleri kullanılarak porlu yüzeylerde yüksek performans elde edilmiştir.  Bu çalışmada AZ91D magnezyum alaşımının yüzeyinin, mikro ark oksidasyon yöntemiyle ve üzerine uygulanan mühürleme yöntemiyle korozyon dayanımının arttırılması hedeflenmektedir. Mikro ark oksidasyon yönteminde en iyi yüzey özellikleri ve kaplamanın en tutarlı olduğu parametrelerin belirlenmesi için çalışmalar yapılmış, bunun ardından mühürleme yöntemiyle mikro ark oksidasyon işleminde açık kalan noktaların iyileştirilmesiyle yüzeyin korozyon direnci arttırılmıştır.

Magnesium alloys are preferred by their low density, accordingly their lightness in many industrial field and also our daily life. Especially new legal regulations, environmental awareness, strict audits and environmental actions are push people to take precautions for pollution and people started many projects for this. Magnesium is mainly used in aircraft, aerospace and automotive industrybecause of lightness. Connecting to this, other industrial branchs are affected. Automotive suppliers have to change their raw material with their equivalents because of this notion. Magnesium is used in many parts of cars. From steering wheels to motor block, magnesium can lighten all the parts of vehicles and decrease fuel waste. Thus, vehicles become more economic and more environmentally friendly. Magnesium could not be part of this project easily. Magnesium is more expensive then aluminum so it is not easy to take over it. But regarding the logistic costs magnesium has an advantage by considering aluminum. Additionally magnesium has advantage because of easy machinability. But magnesium is very active element, so it can react with its ambient quickly. This causes many problems. One of this problems is corrosion. Corrosion problems are very difficult to avoid and limit magnesium in many fields. To solve this problem magnesium need extra surface protection. Micro arc oxidation is one of these methods.  Micro arc oxidation is easy to apply, cheap and environmentally friendy way of surface protection. This system works by using electric so doesn't use fossil fuel and doesn't release toxic gases. Regarding to electrolyte it doesn't pollute environment with poisonous chemical contents.  System consists of power supply, anode, cathode, electrolyte, control panel, stirrer and cooling system. For coating, the sample is attached to positive side and depth in electrolyte. Cathode is attached to negative side of electric system. Parameters are defined by using control panel and coating starts. When applied voltage reaches breakdown voltage, arcs starts at the surface of sample. Thus, oxidation occurs. This operation can be done voltage controlled, current controlled, frequency controlled or pulse controlled. We can choose proper parameter for obtaining proper surface. Also, we can enhance tribological properties, surface hardness and roughness of materials by changing chemical contents of electrolytes. Also we can add many agent for developing surface quality and appearance of material. This way is used for decorative applications.  Also we can obtain porous surface by using micro arc oxidation. In some fields this is a required spesification. Especially in medical fields alloys imitate some parts of our body. In these applications porous surface is important to success their aims. But this advantage become disadvantage in some applications. In shipping, aircraft and automative fields there are corrosion attacks from this pores. To protect surface from this problem micro arc oxidation need some other methods. Sealing is one of the protection ways.  Sealing is mainly used for isolation and filling. But some of its applications are used for protecting the surface. In this project micro arc oxidation surface is protected with sealing. After micro arc oxidation, many micro pores and micro cracks occured at the surface and this cause corrosion weakness. For avoiding this many sealant are exprienced. In this thesis, first the most proper micro arc oxidation surface is aimed. To reach this many expriences are done and many parameters are used. Before starting the surface reactions, samples are prepared. AZ91D magnesium alloy is used and its cut approximately 25 mm diameter and 4 mm thickness as semicircle. Then it is abraded with 320, 400, 600, 800, 1000, 1200 ve 2500 # SiC paper. After that surface is cleaned with acetone and distilled water, then dried with air. Electrolyte contained sodium aluminate and potassium hydroxide and while the micro arc oxidation its kept around 30 ˚C. Whole electrical system works with 30 kW power supply. Every single experiment least for 10 minutes. For characterization, microstructure and elemental composition of the samples were examined by an energy dispersive spectrometer (EDS, Oxford Instruments) equipped scanning electron microscope (SEM, Hitachi TM-1000, JEOL JSM 6335F FEG and Philips XL 30 SFEG). Mean surface roughness (Ra) of the samples was measured by using a surface profilometer (Veeco Dektak, 6M). Cross sectional microstructure of the samples was examined by a scanning electron microscope (SEM, Hitachi, TM-1000). The samples were mounted in a hot setting epoxy resin then grounded with SiC abrasive paper up to #2500 and polished with 3 μm diamond suspension. Then all of the cross-section samples were deposited by a thin gold layer to avoid surface over charging. First, micro arc oxidation process is done by current controlled. 3-1A, 5-2 A and 7-3 A current values and 1200-1200-800 duty cycle are used at this exprience. Then voltage controlled coating process is started. For this parameter many values are tried. At 1200-1200-800 duty cycle 300 V-60 V, 330 V-66 V,350 V-70 V,360 V-72 V and 400 V-80 V values are tried. At pulse controlled experiments 360-72 V, 400-80 V, 3-1A and 5-2 A values are used and for every experiment 10/1 positive, 1/1 negative pulses are tested. The other parameter is duty cycle. On the other hand, pulse is related with duty cycle.  After, the best results of micro arc oxidation process is chosen and sealing is started. Three sealing agent are used for this experiment. Sodium aluminate, sodium vanadate and zirconium oxide are tried for sealing. 50 g/l of solution is prepared for each sealing agent. These solutions are impregnated by using vacuum. The sealing system is included solution container, compressor, pressure gauge and timer. While vacuuming pressure is kept approximately 0,8-0,9 bar and the process long 10 minutes. Then, sample surfaces is examined via scanning electron microscope. Then samples are put in %10 NaCl solution. Samples are followed for a period of time and at every lap samples are weigh and taken photos of them. When scanning electron microscope photos from surface and cross section, coating thickness, surface roughness and chemical content of coating are evaluated together, decided that this is not convenient way for coating. Coating seperates from the surface some of the samples. Second, micro arc oxidation process is done by voltage controlled. When all of the datas are compared 400-80 V value is approved. For pulse controlled experiments, seen that voltage and current base pulse controlled samples have opposite behaviours. Voltage base pulse controlled samples have very thin coating but current base pulse controlled samples have thick and irregular coating. Thus, this type of experiments are not approved. Duty cycle controlled experiments are also done. When they are examined form cross section it is seen that coating seperates from surface. To sum up, best coating is obtaing by using 400-80 V voltage controlled experiments and the surface is proper for sealing process. For sealing process 3 sealing agents and 1 only micro arc coated samples are used. This trial is time controlled. Every solution is vacuumed for 3 times. Then these sample surfaces are controlled via scanning electron microscope.  Zirconium base sealing solution is precipitated on sample quickly but it is not durable enough for physical interferences. When it is examined in scanning electron microscope, its surface is bright and rough. Because of its sandy appearance micro arc surface can not be seen. So we can not decide pores are filled or not.  Vanadate base solution also precipitated easily and it is durable enough for phsical effects. When it is examined via SEM it is seen that surface seem like snow flakes. Pores and micro cracks are filled completely. The sample sealed with aluminate base solution has the best surface appearance. All the pores and micro cracks are filled.  After sealing process, all the samples are put into %10 NaCl solution and they are controlled by period of time. Their surfaces are examined and weighed. All the results are presented in result chapter.
Improving Surface Properties Of Az91d Magnesium Alloys By Using Micro Arc Oxidation And Sealing Methods
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2014
Keywords: Mikro Ark Oksidasyon; Mühürleme; Magnezyum; Micro Arc Oxidation; Sealing; Magnesium